Results of Response Analysis Against the Use of Multimedia Comic Media Man Nusantara (MANTRA) for Civics Learning in Senior High Schools - Bagus Prasetia; Ida Putri Rarasati; Mochamad Yusuf Zen (JOSAR (Journal of Students Academic Research), 2022)
With the lack of learning media, monotonous learning and misuse of cellphones during learning are the reasons for researchers to develop learning media based on PPKn multimedia in high school. The purpose of developing MANTRA media. To see the response of teachers and students to the MANTRA multimedia comic media. The research design used is research and development design. While the approach used is a quantitative approach, where in calculating the data using numbers. This study aims to determine the feasibility of the product developed by the researcher in the form of a multimedia comic insight into the archipelago (mantra). It is hoped that this research can provide benefits towards the development and advancement of science and information technology to support Civics learning in high school. The results in this study are in the form of multimedia comic videos (software) designed using the Corel Draw application in the form of MANTRA learning videos. To assess the feasibility of the product, three experts were validated, namely material, media and language experts who obtained an average score of 74% with a fairly valid category. Meanwhile, product trials to determine student and teacher responses to the developed media scored an average of 87.7% and 78.2% with a very high response to media category.